International relations theory - Viotti, Paul R. (Longman, 2012)
Combining extensive commentary by the authors and excerpts from original scholarship, International Relations Theory evaluates all the major theoretical perspectives that political scientists use to analyze world politics. This unique survey/reader not only looks at classic international relations theory but takes into account changes in the world and important developments in the field. Highly regarded for its lucid and comprehensive coverage, International Relations Theory explains the role of theory in studying world politics and invites readers to critically engage the field's many controversies.